Una súplica por nuestro futuro: lenguaje, tecnología y la lente masculina - Claudia Herbst (Universitat de Barcelona, 2005)
This essay takes a look at the vital role of code literacy in women’s futures and argues that the future of women’s opportunity to participate in the definition of knowledge, its construction and dissemination, is intricately tied up in the developments that are currently taking place at the junction where language and technology intersect. My claims are bold and at the heart of them, the question of literacy –an exclusionary mechanism that historically has been applied in the oppression of women– rears its gendered head. The ensuing discussion is deliberately polemical and proposes that the future of feminism lies in the realm of technology.